Factors Affecting the Community Welfare of Yellow Corn Farmers in Kabangka District, Muna Regency - Waode Syamsinar; Ilma Sarimustaqiyma Rianse; Fahria Nadiryati Sadimantara (International journal of technology and education research, 2025)
The welfare of farmers can be influenced by various welfare factors, namely experience, income, selling price and number of dependents of the family. This study aims to determine the factors that affect the welfare of yellow corn farmers in Kabangka District, Muna Regency. This research was conducted in February-March 2022. Respondents in this study amounted to 32 people with the determination of the sample using random sampling. Data analysis used multiple linear regression with the help of SPSS 20. The results showed that (1) Based on the Good Service Ratio (GSR) yellow corn farmers in Wataliku Village, Kabangka District, Muna Regency were more dominantly less prosperous (84.36%) compared to prosperous farmers. (15.63%). (2) The average income obtained by yellow corn farmers in Wataliku Village, Kabangka District, Muna Regency harvest season is Rp686,912. (3) The factors that significantly influence the welfare of yellow corn farmers are experience (X1), while those that do not significantly affect the welfare of yellow corn farmers are income (X2), selling price (X3) and the number of dependents of the family (X4). Based on the results of the simultaneous calculation of the effect of trust, network, social norms and participation on cooperative management, at a significant level of 10%, the Fcount value is 1.130 with the Ftable value of 1.703